ANALISIS STRATEGI SMK3 BERKELANJUTAN DENGAN PENDEKATAN SWOT PADA KONTRAKTOR LISTRIK DI PADANG - Primayota, Riren; Carlo, Nafryzal; Heldi, Heldi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
The lack of workers' understanding of the importance of OHS (Occupational Health and Safety) contributes to the high rate of workplace accidents in electrical projects. This study aims to identify internal and external factors affecting the implementation of OHS Management Systems (SMK3) among electrical contractors and to formulate strategies using SWOT analysis. Data was collected through observations and questionnaires, then analyzed using IFAS, EFAS, IE Matrix, and SWOT.The IE Matrix results indicate that the company is in the